Adaptability of pullets from cages to a large cage aviary unit system during the initial settling-in period - Yang, Liu; Tong, Qin; Shi, Haipeng; Chen, Gang; Shi, Zhengxiang; Zheng, Weichao; Li, Baoming (International Journal of Agricultural and Biological Engineering, 2018)
Pullets often raised in cage system from week 1 to week 13 in China, when transferred to aviary system after, there will be a problem with adapt. A large cage aviary unit (LCAU) system was developed, which allocated with facilities such as ramps to help cage reared hens to adapt to the multi-tier space. To investigate hens’ adaptability to the new system, space use over time in the LCAU system during the first 10 days after hens transferred were recorded, instantaneous scan sampling and continuous focal sampling were used to assess the behavior difference of hens between the LCAU and conventional cage (CC) systems. On the first day of arrival, 10.03% of hens reached the second tier (S2) and the third tier (S3) of the aviary. During the observation period, an average of 2.42% of hens climbed and stayed at the upper tiers every day. Space allowance on floor of the first tier (S1) increased from 444.62 cm2/hen (91 d) to 586.32 cm2/hen (100 d), which was more than 540 cm2/hen in the CC system. Comfort behaviors in the LCAU system were significantly more than in the CC system (p<0.01) and hens performed more comfort behaviors with the increase of days after transferred. Hens ate and drank less in the LCAU system in the beginning, however, with the increasing use of upper space, hens ate and drank more and more in the LCAU system during the 10 days after transferred from CC system. Consequently, there were no difference of feed behavior between the CC and LCAU systems (p>0.05) on the last 5 days of the whole observing period. The results indicated that hens gradually learned to use the 3-dimensional space in the initial settling-in period and, gained a good welfare condition in LCAU system. Further studies are needed to investigate the three-dimensional preferences and behavior expression in difference period to bridge the gap in knowledge of space use capacity among adult laying hens.Keywords: large cage aviary unit, laying hen, welfare, comfort behaviors, adaptabilityDOI: 10.25165/j.ijabe.20181105.3216Citation: Yang L, Tong Q, Shi H P, Chen G, Shi Z X, Zheng W C, et al. Adaptability of pullets from cages to a large cage aviary unit system during the initial settling-in period. Int J Agric & Biol Eng, 2018; 11(5): 70–76.